Tricuspid valve thrombus causing acute pulmonary embolism - Gunduz, Yasemin (BMJ Publishing Group, 2013)
The development of thrombus on the tricuspid valve is very rare in adulthood and it needs special attention in clinical practice as it can be confused with vegetation or a tumour. Embolisation due to thrombus may have an acute and unexpected course with a detrimental prognosis and a high death rate during the first 24 h after diagnosis. In this report, we presented a case of mobile tricuspid valve thrombus detected by transthoracic echocardiography that led to recurrent pulmonary embolism.